Hubungan Titer Widal Dengan Limfosit Dan Trombosit Pasien Demam Tifoid Di Puskesmas - Geovani R Lubu Pati; Previta Zeizar Rahmawati (Media Husada Journal Of Nursing Science, 2026)
Background: Typhoid fever is a systemic infection caused by Salmonella typhi that leads to hematological abnormalities, including thrombocytopenia and relative lymphocytosis, due to the effects of endotoxins on bone marrow. The Widal test is still widely used as a serological examination in primary health care; however, the correlation between Widal titer and hematological parameters remains inconsistent. Objective: To analyze the correlation between Widal antibody titer and lymphocyte and platelet counts in patients with typhoid fever at Puskesmas. Methods: This was a retrospective cross-sectional analytical observational design. Data were obtained from the medical records of typhoid fever patients at Puskesmas Dau from January to December 2024. Samples were selected using purposive sampling based on inclusion criteria: patients with typhoid fever who had results for Widal titers O, H, PA, PB, lymphocyte and platelet count, and complete medical records. Exclusion criteria included patients with other diagnoses, such as dengue fever and incomplete data. Data analysis was performed using Spearman’s Rank Correlation test with a significance level of p < 0.05. Results: The results showed no significant correlation between Widal titer and lymphocyte count, but a significant negative correlation between Widal titer and platelet count, with r = -0.146 and p = 0.039 [p < 0.05]. This indicates that higher the Widal titer, the lower the platelet count tends to be. Conclusion: There is no correlation between Widal titer and lymphocyte count. There is a significant but very weak negative correlation between Widal titer and platelet count in typhoid fever. These findings are consistent with the pathophysiology of typhoid fever, specifically thrombocytopenia resulting from the effect of S. Typhien dotoxin on bone marrow.